A narrative approach to dealing with trauma in refugee children through Social Case Work Practice. - Reena Cherian (Journal of Social Work Education and Practice, 2023)
According to the United Nations Convention on the Rights of the Child (UNHCR) India has 2 million people of concern or refugees residing in India and over 25,000 asylum seekers in Delhi alone (Sharma, 2009). For reasons such as human rights violations, lack of freedom and protection, and widespread poverty, many refugees and asylum seekers chose to migrate to different countries. India is a refuge for individuals from several nearby countries. The refugees face layers of crisis such as financial, psychological, and political in-terms of citizenship and rights. This paper highlight risks in the form of isolation, identity crises, and several mental health issues that the younger population of refugees and asylum seekers face. Studies show that Social Work methods especially Social Case Work interventions focusing on the narrative approach are an effective method in resolving the issues faced by the refugees. The paper deals with the narratives where the practice experiences of child refugees and asylum seekers were studied using methods with 12 case workers. The paper also lists challenges and opportunities for case workers subscribing narrative approach.